If it's not what You are looking for type in the equation solver your own equation and let us solve it.
142=x-8(1-3x)
We move all terms to the left:
142-(x-8(1-3x))=0
We add all the numbers together, and all the variables
-(x-8(-3x+1))+142=0
We calculate terms in parentheses: -(x-8(-3x+1)), so:We get rid of parentheses
x-8(-3x+1)
We multiply parentheses
x+24x-8
We add all the numbers together, and all the variables
25x-8
Back to the equation:
-(25x-8)
-25x+8+142=0
We add all the numbers together, and all the variables
-25x+150=0
We move all terms containing x to the left, all other terms to the right
-25x=-150
x=-150/-25
x=+6
| -104=-8(x+7) | | 7x-11=3x=5 | | 6(-2k-8)+k=-92 | | -3(x-4)=2x-13 | | 5c+3(8–c)=8 | | -16(3-2x)=432 | | 8(b-6)+3=-85 | | 3.5=y/2 | | 15-2(a-4))=13 | | X+18x3=90 | | 6w+30=3(w+5) | | x=3/10+(x+14) | | 3/10z=0 | | -8=1.8c+32 | | 6/7(7/6x)=6/7(7) | | x=3/10+14 | | x+2(4-x)=2x-6-3x | | 18=3x-2(x-5)=0 | | 5(w-5)=-3w+15 | | 2(-6w+2)-3w=3(w-1)-4 | | 5(x+8)+x=88 | | 3u-12=-23 | | 3(x+1)-9=24 | | -132=6(4x+2) | | -9x-6=-3(2x-1)+6 | | -4x-6=2(x-9) | | -104=8(6x+5) | | 2y-(-7)=13 | | 3/2=n/20 | | 7x+6=69. | | 6(4r+3)=210 | | f(20)=4+8 |